In-community vision testing device development using a Kaupapa Māori framework - Jason Turuwhenua; Joanna Black; Misty Edmonds (Kōtuitui)
We report on a 2019 project in which we ran in-community testing of a novel device for measuring visual acuity (the measure of performance obtained by an eye chart). This work was a collaboration with a community partner school, Kia Aroha College (KAC), a dual Māori/Pacific medium school in Ōtara, South Auckland, New Zealand. Our approach was informed by Kaupapa Māori principles (KM) that centred the school in the research process and emphasised benefits for the community and participants. The result was an event that embedded research activities within a larger health or ‘Hauora Day’ comprising physical and psycho-social assessments, and eye testing. Benefits for the community included direct onsite access to eye health care and on-site follow-up, as well as increased interactions with health personnel and researchers. Benefits for the research team included establishing a valuable adjunct to more typical laboratory based measurements, establishment of a community partner relationship, a more diverse range of clinical exposures for optometry students, and opportunities for cultural competence improvement. Central to this approach is the importance of trusted relationships and mutual benefit. This model requires staffing resources and planning to ensure that the community relationships are maintained, and ideally, strengthened through time..